Effect of binaural beats on pain, anxiety, and procedure tolerance in patients undergoing colonoscopy without sedation: A randomized controlled trial - Demirci, Selim; Sezer, Semih; Pirinççi Sapmaz, Ferdane (The European Research Journal, 2025)
Objectives: This study aimed to investigate the effect of binaural beats on pain, anxiety,and tolerance during colonoscopy of patients without sedation. Methods: This is a prospective, randomized, controlled, single-blind procedural study that included 92 Turkish patients who underwent colonoscopy. The patients were randomly divided into two groups: the binaural beat music group (n=46) and the control group (n=46). The binaural music group was subjected to music through headphones during the colonoscopy, while the control group was provided headphones without music. The anxiety levels were measured using a Visual Analog Scale for Anxiety (VAS-anxiety), while the pain levels were assessed using a Visual Analog Scale for Pain (VAS-pain). Hemodynamic changes, procedure tolerance, cecal insertion and withdrawal times, polyp detection, and patients’ experiences related to colonoscopy were recorded. Likert scales, indicating procedure satisfaction, were also administered immediately after the colonoscopy. Results: The music group demonstrated significantly lower anxiety scores compared to the control group, along with better tolerance scores, a higher willingness to repeat the procedure, and a significant preference to listen to the same music again for any upcoming unsedated colonoscopy procedures (P0.05). Conclusions: For patients undergoing colonoscopy without being sedated, listening to music composed of binaural beats demonstrated a significant decrease in anxiety levels and improved patient tolerance during the procedure, presenting an alternative to sedative medications.